Penguatan Gerakan Sosiokultural Sebagai Upaya Pencegahan Destruktif Kebangsaan - Abdul Rahman; Nurlela Nurlela; Rifal Rifal (Seminar Nasional LP2M UNM, 2019)
This article describes the importance of the socio-cultural movement in an effort to strengthen the Indonesian spirit in the midst of increasingly globalized relations between nations. Admittedly, there is a kind of anxiety over Indonesia that is plural and multicultural in the verge of fighting among fellow children of the nation because of disagreements in the management of national and state life. The founders of this nation have taken pains to frame Indonesia in one knit together by setting aside differences. Therefore, when the ideals of the founders of this nation must be buried with ideas that negate the Unitary State of the Republic of Indonesia based on Pancasila, all efforts and efforts must be mobilized to contain it. The majority Muslim community in this country must take the role of maintaining the sovereignty of the Indonesian state while still striving to advance the nuances of humanity and avoid the path of violence so that Islam can show its existence as a blessing for all life.